2023
DOI: 10.1002/cam4.5686
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of oral human papillomavirus infection in healthy population and head and neck cancer

Abstract: The global incidence of head and neck cancer (HNC) is about 660,000 cases, with a mortality of 325,000 patients annually. 1 Tobacco consumption (smoking and smokeless) has contributed to an increased incidence of HNC (6.1 per 100,000 women and 20.9 per 100,000 men) in the Indian subcontinent, accounting for one-third of the global burden. 2 The recent increase in HNC in nonsmoking, nonalcoholic young individuals is primarily attributed to mucosal high-risk human papillomavirus (HR-HPV) infection. 3 Though Zur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 114 publications
(243 reference statements)
1
7
1
Order By: Relevance
“…Regarding the prevalence of HPV infection in HIV+ patients, our study showed a prevalence of 19.7%, in line with values reported in literature, ranging from 11% to 35% [26,[47][48][49][50][51]. As expected, the prevalence was higher than that reported, on average, for the general population (4.8%) [48], although literature shows that HPV infection can be prevalent also in healthy individuals, with highly variable percentages [30]. The difference between general and HIV+ populations, however, can be explained by the higher virulence of HPV in HIV+ patients, which is due to a reduced host immune response, an increased susceptibility to infection, and to the direct interactions between the two viruses, e.g., HIV is able to increase the expression of HPV E6 and E7 oncogenes [52].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the prevalence of HPV infection in HIV+ patients, our study showed a prevalence of 19.7%, in line with values reported in literature, ranging from 11% to 35% [26,[47][48][49][50][51]. As expected, the prevalence was higher than that reported, on average, for the general population (4.8%) [48], although literature shows that HPV infection can be prevalent also in healthy individuals, with highly variable percentages [30]. The difference between general and HIV+ populations, however, can be explained by the higher virulence of HPV in HIV+ patients, which is due to a reduced host immune response, an increased susceptibility to infection, and to the direct interactions between the two viruses, e.g., HIV is able to increase the expression of HPV E6 and E7 oncogenes [52].…”
Section: Discussionsupporting
confidence: 91%
“…Cross-sectional studies on Italian HIV+ men (predominantly men having sex with men, MSM) showed that oral HPV DNA could be detected in approximately 20% of cases, which is to a much lower extent compared to anal sites [26][27][28][29]. To interpret this data, it is important to highlight that also the global prevalence of oral HPV infection in healthy individuals can be relevant, ranging from 0.67% to 35% [30]; the oral cavity contains a wide spectrum of HPVs, with beta types representing the predominant genus [31]. In the general population, HPV has been found to be more prevalent in males, while subclinical oral HPV infection was detected more frequently in adults aged under 40 or over 60 years [32].…”
Section: Introductionmentioning
confidence: 99%
“…The HPV6, HPV11, HPV16, HPV18, HPV31, HPV33, HPV45, HPV52, and HPV58 strains are accounting for 90% of HNC cases ( 24 , 26 , 113 ). The percentage of HPV positivity varies with the type of HNCs and the different geographic regions ( 26 , 27 , 113 117 ), the highest incidence being reported for sub-Saharan African region (HPV has been identified in 50% of oropharyngeal cancers, 27% of laryngeal cancers, and 23% of oral cavity cancers, with the predominance of HPV16 ( 118 ).…”
Section: Hpv Viral Components and Molecular Genetic And Epigenetic Me...mentioning
confidence: 99%
“…Most studies have determined the presence of HR-HPV DNA without evaluating the biomarkers of HPV carcinogenesis (ie, E6/E7 mRNA and p16 protein), thus failing to distinguish between transient and persistent HPV infection. 6 HPV E6/E7 mRNA detection is a gold-standard test for transcriptionally active HPV infection. 7 The modified eighth American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) classification recommends p16 as an HPV surrogate marker in OPC as it correlates with an improved survival rate.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Hence, p16-positive cases must be confirmed by HPV DNA status to consider causality in OPC. 6 To our knowledge, there is a lack of meta-analysis on the proportion of HPV-associated HNC in Indian patients with a high burden of HPV-driven malignancies such as cervical cancer. Therefore, this systematic review and meta-analysis aimed to provide information about HPV prevalence and genotype distribution in HNC in India.…”
Section: Introductionmentioning
confidence: 99%